ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENCEMARAN NAMA BAIK DAN BERITA BOHONG - Kesuma, Derry Angling; Triputra, Yuli Asmara (Faculty of Law, University of Palembang, 2024)
The problem that the author raises is regarding the reason why the Constitutional Court decided to grant part of the judicial review lawsuit filed by Haris Azhar and Fatia Maulidiyanti, and to remove Article 14 and Article 15 of Law Number 1 of 1946 concerning Criminal Law Regulations regarding the spread of fake news or hoaxes. by using normative legal research methodology, The Constitutional Court has decided and granted part of the judicial review lawsuit filed by Haris Azhar and Fatia Maulidiyanti, which then removed Article 14 and Article 15 and Article 310 of Law Number 1 of 1946 concerning Criminal Law Regulations regarding the spread of fake news or hoaxes.